Penerapan Sistem Bagi Hasil antara Pemilik Modal dan Pengelola Usaha Bahan Bangunan dalam Perspektif Ekonomi Islam - Fitri Melinia; Irwan Habibi Hasibuan (STEBI Global Mulia Cikarang, 2021)
Mudharabah is a contract between two parties (people) who bear each other, one party surrenders his property to another party to be traded with a part that has been found from the profits, such as half or one third with predetermined conditions. The same is true for capital owners and building materials business managers in Bayur Kidul Village, Cilamaya Kulon District, Karawang Regency. There are parties who provide capital to the building materials business manager to be developed into a business selling building materials, both of which are then sold in the city or outside the city. With various kinds of building materials, but there are still many conflicts because there is no written evidence related to the problem when there is damage to the vehicle (truck) to run the building materials business. The aim is to find out and analyze the application of a profit-sharing system between capital owners and business managers to suit the Islamic economic perspective. To find out the profit-sharing system between capital owners and business managers to suit the Islamic economic perspective. To understand the contract used at the time of profit sharing between the owner of the capital and the manager of the business so that it is in accordance with Islamic economic law. This study uses a qualitative approach because this study analyzes and describes a profit-sharing system between the owner and manager of the building materials business in Bayur Kidul Village, Cilamaya Kulon District, Karawang Regency. Based on the results of the study that the profit sharing carried out by capital owners and building materials business managers in Bayur Kidul Village, Cilamaya Kulon District, Karawang Regency is not in accordance with the Mudharabah concept, because there is still no agreement on handling problems in vehicle damage (trucks) to run a building materials business. and there is no written evidence of an agreement, then conflicts often occur between the two parties